2017
DOI: 10.1039/c7ra03872k
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of azo dye with activated peroxygens: when zero-valent iron meets chloride

Abstract: Selection of the most appropriate Fe-based peroxygen oxidation technology depends on the dye wastewater constituents and pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…1821 Therefore, the Fenton or Fenton-like reactions generally occur at the solid–liquid interfaces, where the iron remains substantially in the solid phase either as a mineral or as an adsorbed ion. 18,22 In particular, carbonaceous materials, such as activated carbon (AC), 20,23,24 carbon nanotubes (CNTs), 18,21,25 mesoporous carbon, 26 and carbon aerogels, 20,27 have been well proven as catalyst carriers to immobilize the iron species because of their special performance as a cocatalyst. Recently, Voitko et al 28 reported that graphene oxide (GO) showed better degradation performance than CNTs and AC, which was attributed to the many oxygen-containing functional groups of the GO plates.…”
Section: Introductionmentioning
confidence: 99%
“…1821 Therefore, the Fenton or Fenton-like reactions generally occur at the solid–liquid interfaces, where the iron remains substantially in the solid phase either as a mineral or as an adsorbed ion. 18,22 In particular, carbonaceous materials, such as activated carbon (AC), 20,23,24 carbon nanotubes (CNTs), 18,21,25 mesoporous carbon, 26 and carbon aerogels, 20,27 have been well proven as catalyst carriers to immobilize the iron species because of their special performance as a cocatalyst. Recently, Voitko et al 28 reported that graphene oxide (GO) showed better degradation performance than CNTs and AC, which was attributed to the many oxygen-containing functional groups of the GO plates.…”
Section: Introductionmentioning
confidence: 99%
“…10, the oxidation efficiency is 54.35%, 67.25%, 76.95%, and 81.88% at of 20 C, 40 C, 60 C, and 80 C, respectively. The oxidation process of methyl orange indicates that molecular conjugate chains are gradually shortened, 41,42 which can be reected in the UV spectrum. The oxidation of methyl orange typically involves the cleavage of the azo bond, the breakdown of the benzene ring, and the formation of small inorganic molecules; these steps are described as decolorization, degradation, and mineralization in this study.…”
Section: A Synergistic Combination Of Three Ows For the Step-aop Minmentioning
confidence: 99%
“…It is well-known [ 46 , 47 , 48 ] that the oxidation process of the azo dyes typically begins with a break of the azo bond (a decolourization stage). It is then followed by the degradation of benzene ring in the dye molecule to finally undergo complete or partial mineralization process.…”
Section: Resultsmentioning
confidence: 99%
“…It is then followed by the degradation of benzene ring in the dye molecule to finally undergo complete or partial mineralization process. These effects could be visualized by absorbance changes within the UV-VIS spectrum for the selected wavelength ranges, namely: 350–600, 265–350 and 200–265 nm, correspondingly [ 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation